Multiple phases of ice-dammed lake formation and drainage associated with a surge of Shisper Glacier, western Karakoram - Harold Lovell; Sher Muhammad (Journal of Glaciology)
Glacier surges can create ice-dammed lakes when the advancing terminus blocks drainage. Such lakes are inherently unstable and can drain abruptly as glacial lake outburst floods (GLOFs), presenting a hazard to downstream populations and infrastructure in high mountain environments. We present satellite image analysis of the evolution of an ice-dammed lake formed by the 2018–20 surge of Shisper Glacier, western Karakoram. Our analysis identifies six phases of lake evolution. A large lake of up to 33.7 ± 9% million m3 formed in 2018–19, 2019–20, 2020–21 and 2021–22. In each case, the lake began to fill late in the year, reached a maximum size in May, and had completely drained between May and July, typically over 1–2 days. This analysis provides further evidence that GLOF hazards associated with lakes dammed by glacier surges can persist for several years after surge termination.